Analysis of stability of a Power System by using Delay Static State Feedback (2012)
This article presents the analysis of stability of a power system modeled as Infinite Bus Connected Generator with delay static state feedback. The model of the power system is described by nonlinear differential- algebraic equations. For controller design, we linealize the nonlinear differential-algebraic model around an operation point to obtain a lineal differential-algebraic model. As of this model obtains the Kronecker -Weierstrass model which designs the controller. To obtain the K gain of the controller outline inequalities matrix lineal (LMI's ). Then it makes a study of the maximum delay that it supports in the state feedback. At the end of the article present the results and the conclusions.